Identification of gene–sun exposure interactions of GWAS-identified variants in perceived facial aging progression - Obry, Ludivine; Medina-Santos, Raissa; Rahmouni, Myriam; Noirel, Josselin; Labib, Toufik; Galan, Pilar; Spadoni, Jean-Louis; Gendronneau, Gaëlle; Jdid, Randa; Courrèges, Sandra; Latreille, Julie; André, Nada; et al. (Frontiers in Aging, 2025)
BackgroundSkin aging is characterized by observable major changes in the composition and organization of the skin, including the appearance of wrinkles, tissue sagging, dryness, and pigmentary disorders. While both environmental and genetic factors contribute to these changes, their interaction remains underexplored. Perceived age is a biomarker of health and strongly related to facial skin aging features. Thus, we conducted a gene-environment interaction analysis on the perceived facial aging progression phenotype in 226 women, focusing on sun exposure as the environmental factor.MethodsWe assessed perceived age in 226 women at two time points, 12 years apart, allowing defining a perceived facial aging progression as phenotype. We applied a two-step gene-environment interaction approach. First, a genome-wide association study (GWAS) was performed to identify SNP effects on the perceived facial aging progression, selecting those with a p-value <5 × 10−3. In the second step, we used GEM software to test interactions between the 7,464 selected SNP and sun exposure.ResultThe GWAS identified four significant SNP associated with perceived facial aging progression, located in the CGGBP1, PGM5-AS1, and CSMD1 genes. The CGGBP1 gene is involved in DNA damage/repair, telomere and mRNA metabolism; PGM5-AS1 is an antisense RNA regulating PGM5, a component of adherens-type cell junctions; CSMD1 is involved in complement regulation and cell migration. In the second step, we tested 7,464 SNP for interactions with sun exposure in perceived facial aging progression, identifying a significant interaction signal in the VANGL1 gene. The VANGL1 gene contributes to the structural organization of the plasma membrane and has been identified as a key gene for cutaneous function and was expressed during keratinization.DiscussionThis study revealed four relevant genetic associations with skin aging and one significant G × E interaction. These findings support the known link between telomere shortening/protection and aging, and suggesting a potential role for keratinization in the context of facial aging and sun exposure, though further validation in larger cohorts is necessary. The findings could help to develop new approaches for facial aging prevention and treatment and to better understand molecular mechanisms of aging.